A case of methotrexate resistant gestational trophoblastic neoplasia - Singh, Sanjay; Singh, Akhileshwar; Vardhan, Shakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Gestational trophoblastic neoplasia (GTN) is a subset of gestational trophoblastic disease (GTD) which has a propensity to invade locally and metastasize. Patients with low risk GTN generally respond well to single agent chemotherapy (methotrexate (MTX) or actinomycin-D (ACT-D). However, high risk cases may develop resistance or may not respond to this first-line chemotherapy and are unlikely to be cured with single-agent therapy. Therefore, combination chemotherapy is used for treatment of these cases. Here we present a 25 years old P2 L2 A1 lady, who was initially treated at a peripheral hospital with multiple doses of Injection methotrexate with a working diagnosis of persistent trophoblastic disease. She didn’t respond to this treatment and reported to our centre for further management. On evaluation she was found to be a case of high risk GTN (invasive mole) (I:8) for which she was put on combination chemotherapy in the form of Etoposide-Methotrexate-Actinomycin-Cyclophosphamide-Oncovin (EMA-CO) regime. She responded to this treatment and is presently asymptomatic and is under regular follow up.